A statistical analysis of companies' financing strategies in Portugal during the COVID-19 pandemic - Fernando A. de Oliveira Tavares; Eulália Maria Mota Santos; Mafalda Venâncio de Vasconcelos; Vasco Capela Tavares (Journal of Risk and Financial Management, 2023)
This study aims to establish which sources of financing were used and the relevance of different banking products for Portuguese companies during the pandemic. We also intend to understand the determinants of companies' financing options and what lies behind their decisions concerning the appropriate level of debt. A quantitative methodology was used, based on a questionnaire given to Portuguese companies to analyse different financing issues. The sample was composed of 1957 companies with a business volume of more than EUR 500,000 per year. The results show that Portuguese companies focused on managing liquidity and corporate risk. We found evidence that companies kept financing themselves by banking products such as in the pre-pandemic period, although 29.6% resorted to the LAE-COVID economy support line. Companies decide on the appropriate amount of debt based on the nature of the business, the phase of the life cycle in which the company is, the cash flows' volatility, accounting results, credit rating, and fiscal benefits. Academicians and companies should master the concept of company financing and adopt strategies to consider the level of debt and refine the banking products to be used. Although the literature on business financial management usually claims that all crises are the same, the COVID-19 pandemic not only caused a recession but also forced people and companies to adapt to a new environment. Portuguese companies have shown resilience and focus on their adoption of good financing practices.
Keywords: 650; alternative forms of financing; credit evaluation; financial management; financial structure; financing strategies